Method for forecasting the time standard of multi‐characteristic item - Hadad, Yossi; Friedman, Lea (Technological and Economic Development of Economy, 2005)
The purpose of this paper is to propose a method for determining the time standard of items based on several characters, where part of them is quantitative and some of them are qualitative (dichotomic). The method of determining the time standard of an item is based on Multiple Linear Regression where the dependent variable is the time standard for the production of a lot size of item and the characters of the item are the independent or regressor variables. In this paper we introduce the method for determining the time standard of an item, the way for measuring the qualitative independent variable. The method is illustrated on a case study in an Israeli plant in its research department of materials and processes. In this department a great variety of items were produced, each item has different characters. Sudėtingo gaminio laiko normos prognozavimo metodas Santrauka. Šio straipsnio tikslas ‐ pasiūlyti gaminio gamybos laiko normos nustatymo metodą pagal daugelį kintamųjų, iš kurių vieni yra kiekybiniai, o kiti kokybiniai. Gaminio gamybos laiko normos metodas pagrįstas sudėtine linijine regresija. Čia gaminio gamybos laiko norma yra priklausomas kintamasis (masinei gamybai), o gaminio savybės yra nepriklausomi arba regresiniai kintamieji. Straipsnyje aprašomas minėtas metodas, pristatomas kokybinių kintamųjų įvertinimo principas. Metodas taikomas vienos Izrealio gamyklų Medžiagų ir procesų tyrimo skyriuje. Šiame skyriuje buvo pagaminta daug įvairiu savybių gaminių. Reikšminiai žodžiai: prognozavimas, laiko norma, sudėtingas gaminys. First Published Online: 21 Oct 2010